Ketidaksinkronan Sistem Pembinaan antara Pesantren dan Perguruan Tinggi pada Fase Transisi Mahasiswa - Natasya Ainun Fernanda; Mohammad Satriyo; Argi Brilian Pramana (CV. Laskar Karya, 2026)
This study is motivated by the lack of synchronization between the mentoring systems of islamic boarding schools and higher education institutions, which affects the sustainability of value internalization during students’ transitional phase. Differences in mentoring orientation, control systems, and the absence of a structured transition management framework indicate gaps in cross-institutional mentoring management. This study aims to identify forms of system misalignment, analyze the implementation of mentoring that remains partial, and formulate a transition management design as an integrative solution. The research employs a qualitative descriptive approach, with participants consisting of students with islamic boarding school backgrounds, mentoring administrators, and academic staff. Data were collected through interviews, observations, and documentation, while data analysis used an interactive model. The findings reveal that mentoring is not yet integrated, as indicated by program fragmentation, the absence of an integrated curriculum, and weak coordination and evaluation mechanisms. The novelty of this study lies in the development of transition management as an integrative approach. The implications suggest that a structured transition management design can strengthen value sustainability and improve the effectiveness of student mentoring.